A Clear‐Cut Example of Selective BpinBdan Activation and Precise Bdan Transfer on Boron Conjugate Addition1. Issue 13 (24th February 2014) - Cid, Jessica; Carbó, Jorge J.; Fernández, Elena
Abstract Activating the non‐symmetrical BpinBdan diboron reagent with alkoxide leads to the formation of two possible adducts: MeO−→BpinBdan or MeO−→BdanBpin. Experimental and theoretical investigation confirms that the MeO−→Bpin interaction is preferred and thus selective formation of a CBdan bond upon reaction with an activated CC bond.